(untitled) (The Insight, 2023)
Background: Health care providers who are directly involved in the screening, diagnosis, and treatment of COVID-19 patients are at risk of developing psychological difficulties such as depression, anxiety, insomnia, and other mental health problems. The rising number of positive cases, along with overwork, depletion of personal protective instruments, a lack of treatment, and a sense of being under-supported, may all add to the psychological burden of these health care personnel. Objective: The aim of the study was to find out the prevalence of mental health condition by analysis the prevalence of anxiety, depression, and stress. Methodology: It was a cross sectional study conducted among midwives working in Rohingya camp in Cox’s bazar with the sample size of 446. Result: The prevalence of normal mild moderate and severe anxiety, depression and stress reported (24.9%, 27.6%, 26.5% and 21.1%), (23.8%, 20.4%, 32.5% and 23.3%) and (33.6%, 27.8, 20.0% and 18.6%). Conclusion: High anxiety, depression level found and Working environment was directly co related with anxiety, depression and stress among midwives working in Rohingya camp in Cox’s bazar during covid-19.